Pendidikan Karakter Islami dan Pembentukan Kepribadian Anak Melalui Pendidikan - Hani Lailatul Maghfiroh; Nanang Fauzan Yazid Bastomi; M. David Ilham Yusuf; Ahmad Husin (CV. Lentera Literasi Indonesia, 2026)
This study aims to describe and analyze the ability to harmonize intellectual potential with spiritual intelligence. The research focus is directed at educators (teachers/parents) and students as the center for value internalization and personality transformation. This study employs a descriptive qualitative approach with a content analysis method. Data consist of verbal quotes and behavioral descriptions representing aspects of noble character (akhlakul karimah) and spiritual intelligence, including the values of monotheism (tawhid), independence and discipline, etiquette (adab) and ethics, and self-control. The results indicate that the Islamic educational environment and the role modeling provided by educators serve as the primary instruments in internalizing noble character values into the child's soul. Meanwhile, students demonstrate a tangible behavioral transformation, evolving from individuals who initially lacked self-control and tended to be individualistic into figures who are disciplined, honest, and possess social empathy based on monotheistic values. Furthermore, the subjects experience significant personality development, shifting from a lack of empathy to becoming individuals aware of their moral and social responsibilities. This change is influenced by a consistent process of role modeling and an environment that supports the daily habituation of proper etiquette (adab). These findings demonstrate that the integration of Islamic values in education is not merely a transfer of knowledge but a key strategy in building a holistic (kaffah) child personality.